Pengaruh Skarifikasi Benih terhadap Pertumbuhan Tanaman Mucuna bracteata: Effect of Seed Scarification on the Growth of Mucuna bracteata Plants - Darmin, Vinensius; Mullik, Marthen L.; Dami Dato, Twen O. (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
The main problem in the cultivation of Mucuna bracteata is the hardness of the seed coat, which results in low seed dormancy. The aim of this study was to examine the effectiveness of different seed scarification methods on the growth of M. bracteata plants. This research was conducted at Prof. Bale-Therik's farm in Noelbaki Village, Kupang Tengah Subdistrict, Kupang Regency, for 21 days. This research used a completely randomized design (CRD) of 4 treatments and 5 replicates, with each replicate consisting of 15 seeds. The treatments consisted of control (SB0); seeds soaked in warm water at 50°C for 2 hours (SB1); seeds soaked in normal temperature water for 24 hours (SB2); and seeds scarified (SB3). Data obtained during the study were analyzed using analysis of variance to test the effect of treatment with an alpha value of 0.05. Differences between treatments were tested by Duncan's multiple range test. The results showed that seed scarification had a very significant effect (p<0.01) on all parameters measured. SB3 treatment significantly accelerated leaf emergence (6.21 days), number of leaves (27.47 strands), leaf length (15.51 cm), leaf width (9.89 cm), the onset of tendril growth (8.33 days), tendril length (117.16 cm), and tendril growth rate (6.89 cm day-1). It was concluded that the seed scarification technique (SB3) was the best treatment because it could influence and improve the growth of M. bracteata plants. Keywords: dormancy, growth, Mucuna bracteata, scarification